Carbon–Sulfur Bond Formation via Metal-Catalyzed Allylations of Sulfur Nucleophiles - Liu, Wei; Zhao, Xiaoming (Synthesis, 2013)
The development of practical approaches for the construction of carbon–sulfur bonds is of interest to scientists. In particular, carbon–sulfur bond formation by transition-metal-catalyzed allylations has been attracting great attention. Allylic sulfides are important substances owing to their broad applications in synthetic and pharmaceutical areas. The alkene and sulfur moieties in allylic sulfides can lead to numerous transformations. This review details the development of carbon–sulfur bond formation through palladium-catalyzed rearrangements, palladium-catalyzed allylations, iridium-catalyzed regio- and enantioselective allylations and miscellaneous metal-catalyzed allylic substitutions. Carbon–selenium bond formations via metal-catalyzed allylic substitutions are also reviewed.1 Introduction2 Carbon–Sulfur Bond Formation via Palladium-Catalyzed Reactions2.1 Rearrangements of Allylic Substrates2.2 Allylations2.3 Asymmetric Allylations3 Carbon–Sulfur Bond Formation via Iridium-Catalyzed Regio- and Enantioselective Allylations4 Carbon–Sulfur Bond Formation via Miscellaneous Metal-Catalyzed Reactions4.1 Nickel4.2 Ruthenium4.3 Gallium4.4 Iron5 Carbon–Selenium Bond Formation via Metal-Catalyzed Allylic Substitutions6 Conclusions
Keywords: carbon–sulfur bond formation; sulfur nucleophiles; metal catalysts; allylic substitutions; enantioselective allylations; allylic sulfides; allylic selenides